Applied services trade policy: A guide to the Services Trade Policy Database and the Services Trade Restrictions Index - Ingo Borchert; Batshur Gootiiz; Joscelyn Magdeleine; Juan A. Marchetti; Aaditya Mattoo; Ester Rubio; Evgeniia Shannon (World Trade Organization (WTO), 2019)
Better information on how services policies vary across economies and sectors over time would improve the empirical analysis of their impact. This paper describes the Services Trade Policy Database (STPD), a joint initiative by the World Bank and the WTO Secretariat, which builds on a database developed by the World Bank nearly ten years ago and draws on a recent OECD database. The STPD offers comparable information on services trade policies for 68 economies in 23 subsectors across five broad areas - financial services, telecommunications, distribution, transportation and professional services, respectively. The STPD features several improvements. First, data are collected according to a newly developed policy classification, consistent with both the earlier World Bank database and the current OECD database, enabling for the first time a comparison of services policies over a significant period and across a large cross-section of industrial and developing economies. Second, the database contains information not just on core trade policies but also on other increasingly relevant aspects, such as licensing conditions and data restrictions. Third, policy restrictiveness is quantified following a more systematic approach that aggregates the information within a single consistent and transparent framework. Building on these innovations will make it possible to identify global patterns of services trade policies as well as secular trends in policymaking over the past decade.
Keywords: F13; F14; F23; L80; 330; services; trade policy; investment; STRI; trade restrictions; quantification